Small State Regional Cooperation, South-South and South-North Migration, and International Trade - Schiff, Maurice (2012)
This paper provides a different basis than previous analyses for regional bloc formation and regional migration. Due to low bargaining power and fixed costs, small states face a severe disadvantage in negotiations with the rest of the world and might benefit by forming a regional bloc. The study a) presents a general equilibrium model where bargaining power, international and regional negotiation costs, number of issues negotiated, and accession rule to the bloc determine its size and welfare impact; and b) examines the impact of international migration as well as the migration-trade relationship. The main findings are: i) the likelihood of regional bloc formation, its size and welfare impact, increases with international negotiation costs and the number of issues negotiated, and decreases with regional negotiation costs; ii) bloc size is optimal (below the optimum) if an accession fee is (is not) charged; iii) South-South migration raises bloc size and welfare; iv) South-South migration and trade are complements under market access negotiations and are substitutes under negotiations for unilateral transfers as well as under migrant remittances; and v) South-North migration and bloc formation, and South-North and South-South migration, are substitutes for the states that benefit from membership in the bloc.